Fear Stress During Pregnancy Affects Placental m6A-Modifying Enzyme Expression and Epigenetic Modification Levels - Wang, Qiyang; Pan, Mingmin; Zhang, Tong; Jiang, Yu; Zhao, Peiyuan; Liu, Xihong; Gao, Anqi; Yang, Liping; Hou, Junlin (Frontiers in Genetics, 2022)
As the hub connecting mother and offspring, the placenta’s normal development is vital for fetal growth. Fear stress can cause some structural alterations in the placenta and affect placental development and function. N6-methyladenosine (m6A) is the most common mRNA modification and is involved in regulating the development of the placenta and embryo. There are no reports on the potential role of m6A modification in placental damage caused by fear stress during pregnancy. In this study, we demonstrated that fear stress during pregnancy increases the levels of methylated enzymes (METTL3, METTL14, and WTAP), decreases the levels of demethylase FTO, and increases the overall methylation levels in the placenta of pregnant rats. MeRIP-seq data analysis revealed 22,010 m6A peaks associated with 12,219 genes in the placenta of the model and 21,060 m6A peaks associated with 11,730 genes in the placenta of the control. The peaks were mainly concentrated in the coding region and the 3ʹ untranslated region. In addition, 50 genes with abnormal modification and expression (double aberrant genes) were screened out by combining MeRIP-seq and RNA-seq data. Mefv, Erbb2, and Cgas were selected from 50 double aberrant genes, and MeRIP-qPCR and real-time quantitative polymerase chain reaction were used to verify their modification and expression levels. Our findings suggest that m6A modifications play an important role in placental dysfunction induced by fear stress during pregnancy.